"OUR YOUTH CRUISE": THE PROBLEM OF PATRIOTISM YOUNG MAN YEVHEN MALANIUK - Крупач, М. П. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article raised the problem of ideological orientation E. Malaniuka Young man patriotism that prompted him to join the Kiev military school during the First World War.